Development of an Acclimatization Kit as a Learning Medium for Plant Tissue Culture Course - Atika Okta Melisa; Andi Asyhari (Universitas Ahmad Dahlan, 2025)
Plant tissue culture is an important biotechnology technique that requires both conceptual understanding and practical skills. However, learning activities related to plant tissue culture in higher education are often constrained by limited laboratory facilities, resulting in learning processes that rely mainly on theoretical explanations. One critical stage in plant tissue culture is acclimatization, which determines the survival of plantlets during the transition from in vitro to ex vitro conditions. This study aimed to develop an acclimatization kit as a learning medium for the Plant Tissue Culture course in the Biology Education Program at UIN Sunan Kudus. The research employed a Research and Development approach using the 4D model, implemented up to the develop stage. The acclimatization kit was designed using orchid plantlets and simple planting media to support hands-on learning activities. The results indicated that the acclimatization kit was highly feasible in terms of learning aspects, design, and usability. Students responded positively, showing increased motivation, engagement, and understanding of the acclimatization process. In conclusion, the developed acclimatization kit provides an effective and practical learning medium that supports experiential learning in plant tissue culture courses and offers a solution to overcome laboratory limitations in higher education institutions.